2015
DOI: 10.1074/jbc.m114.624742
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Human Primase

Abstract: Background: DNA primase synthesizes RNA primers and is indispensable for genome replication.Results: We present a crystal structure of the intact human primase at 2.65 Å resolution. Conclusion:The long linker between two domains of the large subunit is important for RNA priming. Significance: The obtained data provide notable insight into the mechanism of primase function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
110
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 51 publications
8
110
0
Order By: Relevance
“…1 and 2). These findings help to explain why in previous primer extension studies, where the substrate was missing TriP and sometimes also the 3Ј-overhang, the effect of p58 C deletion was not so prominent, and its significance for primer elongation was underestimated (13,18,33). Earlier, Podust et al (34) compared the activity of Prim-Pol␣ purified from the human placenta on ribooligoadenylates of varying length (from 2 to 10 nucleotides) and found that deletion of the ␤-and ␥-phosphates from the 5Ј-terminus of RNA primers significantly diminishes their extension.…”
Section: P58 C Plays An Important Role In Primer Extension and Lengthmentioning
confidence: 67%
See 3 more Smart Citations
“…1 and 2). These findings help to explain why in previous primer extension studies, where the substrate was missing TriP and sometimes also the 3Ј-overhang, the effect of p58 C deletion was not so prominent, and its significance for primer elongation was underestimated (13,18,33). Earlier, Podust et al (34) compared the activity of Prim-Pol␣ purified from the human placenta on ribooligoadenylates of varying length (from 2 to 10 nucleotides) and found that deletion of the ␤-and ␥-phosphates from the 5Ј-terminus of RNA primers significantly diminishes their extension.…”
Section: P58 C Plays An Important Role In Primer Extension and Lengthmentioning
confidence: 67%
“…Cloning, Expression, and Purification-Cloning, expression, and purification to homogeneity of the human primase het-erodimer (p49-p58; p49 contains 420 amino acids, p58 contains 509), the C-terminal domain of p58 (p58 C ; amino acids 266 -456), primase without p58 C (p49-p58 N ; p58 N contains amino acids , and the human Pol␣ without the catalytic core (p70-p180 C ; p180 C contains amino acids 1265-1462) have been described elsewhere (13,20,21). The complexes p49-p58-p70-p180 C (Prim-Pol␣⌬cat) and p49-p58 N -p70-p180 C (Prim⌬FeS-Pol␣⌬cat) have been obtained in the same way as Prim-Pol␣ (6); the pure primase and Pol␣ samples were mixed at an equimolar ratio and incubated on ice for 30 min, and the reconstituted complexes were purified by gel-filtration on a Superose 12 column (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently solved the crystal structures of human DNA primase and the Pol ␣ catalytic core domain (55,56). Now we have the crystal structures covering all the functional domains of human Prim-Pol ␣ that are necessary for building a model of the entire tetrameric complex.…”
Section: Discussionmentioning
confidence: 99%